Manufacturing method for bipolar electrode stacks

JP2026167216APending Publication Date: 2026-10-14TOYOTA JIDOSHA KK
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2025060673
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-04-01
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0014】 本開示の方法によれば、それぞれ所望の密度である正極活物質層及び負極活物質層を有する電極積層体を製造できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026167216000001
    Figure 2026167216000001
Patent Text Reader

Abstract

The present disclosure aims to provide a method for manufacturing an electrode laminate having a positive electrode active material layer and a negative electrode active material layer having desired densities. [Solution] The present disclosure is a method for manufacturing a bipolar electrode laminate having a first active material layer, a current collector foil, and a second active material layer in that order, comprising: (a) providing an electrode laminate precursor having a first active material layer precursor, a current collector foil, and a second active material layer precursor in that order; and (b) pressing the electrode laminate precursor with a pressing member, wherein the first active material layer precursor contains ethylene carbonate, the ethylene carbonate content in the first active material layer precursor is greater than the ethylene carbonate content in the second active material layer precursor, and in step (b), the ethylene carbonate is at least partially melted.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This disclosure relates to a method for manufacturing a bipolar electrode stack. [Background technology]

[0002] A bipolar electrode laminate is an electrode laminate in which multiple bipolar electrodes are stacked, each having at least a positive electrode active material layer, a current collector layer, and a negative electrode active material layer in that order. For example, bipolar electrodes may be manufactured by coating electrodes with an active material and then pressing them.

[0003] For example, Patent Document 1 discloses a method for manufacturing an electrode, which includes the steps of: forming a first active material layer for a first electrode on the first surface of a first metal foil; pressing the first active material layer with the first surface of a second metal foil containing a different type of metal than the metal of the first metal foil facing the second surface of the first metal foil opposite to the first surface; forming a second active material layer for a second electrode having a different polarity from the first electrode on the second surface of the second metal foil opposite to the first surface after pressing the first active material layer; and pressing the second active material layer. The method described in Patent Document 1 is said to reduce the number of manufacturing steps.

[0004] Furthermore, Patent Document 2 discloses a coating composition for an active material layer, comprising at least an active material, a binder, and an alkyl alcohol having 1 to 5 carbon atoms, wherein the alkyl alcohol is contained in an amount of 0.6 to 1.5% by weight of the total composition. The coating composition for an active material layer described in Patent Document 2 is said to be a coating composition for an active material layer that can stably produce a positive electrode plate for a non-aqueous electrolyte secondary battery that does not produce craters in the active material layer and is excellent in uniformity and homogeneity in thickness, composition, and surface smoothness.

[0005] Furthermore, Patent Document 3 discloses a coating composition for an active material layer, characterized by containing at least an active material, a binder, and a surfactant. The coating composition for an active material layer described in Patent Document 3 is said to be a coating composition for an active material layer that has good adhesion and wettability, and can produce electrode plates with high battery capacity at low cost, with high productivity, and stably.

[0006] Furthermore, in bipolar batteries, while a high density of the positive electrode active material layer is desirable for high capacity, a low to medium density of the negative electrode active material layer is sometimes desired to absorb the expansion and contraction of the negative electrode active material. Therefore, various studies are being conducted to manufacture bipolar electrodes having positive and negative electrode active material layers with the desired densities.

[0007] For example, Patent Document 4 discloses a method for manufacturing a bipolar electrode laminate having a first electrode active material layer, a current collector layer, and a second electrode active material layer in that order, the method comprising the following steps: providing a first electrode composite material comprising a first electrode active material and a first binder, and a second electrode composite material comprising a second electrode active material, a second binder, and an electrolyte component; forming the first electrode composite material on a first surface of the current collector layer to form a first electrode active material layer precursor, and forming the second electrode composite material on a second surface of the current collector layer to form a second electrode active material layer precursor; pressing the laminate comprising the first electrode active material layer precursor, the current collector layer, and the second electrode active material layer precursor; and after pressing, dissolving the electrolyte component in the second electrode active material layer with a solvent to produce an electrolyte. According to the method described in Patent Document 4, the positive electrode active material layer and the negative electrode active material layer can each be made to a desired density. [Prior art documents] [Patent Documents]

[0008] [Patent Document 1] Japanese Patent Publication No. 2021-082504 [Patent Document 2] Japanese Patent Publication No. 2006-172805 [Patent Document 3] Japanese Unexamined Patent Publication No. 2006-107749 [Patent Document 4] Japanese Unexamined Patent Publication No. 2024-175966 [Summary of the Invention] [Problem to be Solved by the Invention]

[0009] As described above, when a layer for forming a positive electrode active material layer is applied to one surface of an electrode and a layer for forming a negative electrode active material layer is applied to the other surface, and these layers are pressed simultaneously to manufacture a bipolar electrode, the respective densities of the positive electrode active material layer and the negative electrode active material layer formed by pressing cannot be sufficiently controlled.

[0010] In addition, even when the method for controlling the densities of the positive electrode active material layer and the negative electrode active material layer formed by pressing as described in Patent Document 4 is used, it has been difficult to form a sufficient density difference between the positive electrode active material layer and the negative electrode active material layer for high capacity enhancement.

[0011] Accordingly, the present disclosure aims to provide a method for manufacturing an electrode laminate having a positive electrode active material layer and a negative electrode active material layer each with a desired density. [Means for Solving the Problem]

[0012] The present disclosure achieves the above object by the following means.

[0013] (Aspect 1) A method for manufacturing a bipolar electrode laminate having a first active material layer, a current collector foil, and a second active material layer in this order, the method comprising: (a) providing an electrode laminate precursor having a first active material layer precursor, a current collector foil, and a second active material layer precursor in this order, and (b) pressing the electrode laminate precursor with a pressing member. comprising, the first active material layer precursor contains ethylene carbonate, The ethylene carbonate content in the first active material layer precursor is greater than the ethylene carbonate content in the second active material layer precursor, and In step (b), the ethylene carbonate is melted at least partially. A method for manufacturing a bipolar electrode stack. (Aspect 2) The method according to embodiment 1, wherein the temperature of the press member is at or above the melting point of ethylene carbonate. (Aspect 3) The method according to embodiment 1 or 2, wherein the pressing member is a roll press. (Aspect 4) The method according to any one of embodiments 1 to 3, wherein the first active material layer is a positive electrode active material layer, and the second active material layer is a negative electrode active material layer. (Appendix 5) The method according to embodiment 4, wherein the negative electrode active material layer contains silicon particles as the negative electrode active material. [Effects of the Invention]

[0014] According to the method disclosed herein, an electrode laminate having a positive electrode active material layer and a negative electrode active material layer having desired densities can be manufactured. [Modes for carrying out the invention]

[0015] The embodiments of this disclosure will be described in detail below. However, this disclosure is not limited to the embodiments described below, and can be implemented in various ways within the scope of the gist of this disclosure. Furthermore, in the description of the drawings, the same elements are denoted by the same reference numerals, and redundant descriptions are omitted.

[0016] ≪Method for manufacturing bipolar electrode stacks≫ The method disclosed herein for manufacturing a bipolar electrode stack is A method for manufacturing a bipolar electrode laminate having a first active material layer, a current collector foil, and a second active material layer in this order, (a) To provide an electrode laminate precursor having a first active material layer precursor, a current collector foil, and a second active material layer precursor in this order, and (b) Pressing the electrode laminate precursor with a pressing member, Includes, The above-mentioned first active material layer precursor contains ethylene carbonate, The ethylene carbonate content in the first active material layer precursor is greater than the ethylene carbonate content in the second active material layer precursor, and In step (b), the ethylene carbonate is melted at least partially.

[0017] According to the above method, an electrode laminate having a positive electrode active material layer and a negative electrode active material layer with a desired density can be manufactured.

[0018] When pressing bipolar electrode laminates, that is, when pressing electrode laminates having a positive electrode active material layer and a negative electrode active material layer on both sides of the current collector foil, the positive electrode active material layer and the negative electrode active material layer are pressed simultaneously, making it difficult to control the density of each layer to an appropriate density. Furthermore, since the negative electrode active material is prone to expansion and contraction, it is generally considered preferable for the negative electrode active material layer to be less dense than the positive electrode active material layer, or in other words, for better battery performance, the positive electrode active material layer to be denser than the negative electrode active material layer.

[0019] In contrast, the Disclosing Party has found that by using an electrode mixture containing ethylene carbonate and pressing the electrode mixture while the ethylene carbonate is molten, the ethylene carbonate in the electrode mixture can be used as a lubricant to promote the compaction of the active material layer by pressing.

[0020] Based on this understanding, the method of the present disclosure provides a method for manufacturing a bipolar electrode laminate having a first active material layer, a current collector foil, and a second electrode active material layer in that order, wherein the ethylene carbonate content in the precursor of the first electrode active material layer is greater than the ethylene carbonate content in the precursor of the first electrode active material layer, and densification in the first electrode active material layer can be promoted by pressing while at least partially melting the ethylene carbonate.

[0021] Furthermore, since ethylene carbonate is a solid at room temperature (25°C) and is an electrolyte component, it is unnecessary to dry and remove the ethylene carbonate after the formation of the active material layer. Therefore, this disclosure can be effectively utilized even when the entire active material layer formation process is carried out as a dry deposition process.

[0022] <Bipolar electrode laminate> In this disclosure, the bipolar electrode laminate comprises a first active material layer, a current collector foil, and a second active material layer in that order.

[0023] (First and second active material layers) In this disclosure, the first and second active material layers are included in the bipolar electrode stack.

[0024] The first and second active material layers of this disclosure include an active material. The first and second active material layers of this disclosure may further optionally contain at least one of a dispersant, a conductive additive, a solid electrolyte, and a binder.

[0025] In this disclosure, the first active material layer may be a positive electrode active material layer or a negative electrode active material layer. If the first active material layer is a positive electrode active material layer, the second active material layer may be a negative electrode active material layer, and if the first active material layer is a negative electrode active material layer, the second active material layer may be a positive electrode active material layer.

[0026] When the first or second active material layer is a positive electrode active material layer, the first or second active material layer contains at least a positive electrode active material. When the first or second active material layer is a negative electrode active material layer, the first or second active material layer contains at least a negative electrode active material.

[0027] The material of the positive electrode active material is not particularly limited. Examples of the positive electrode active material include lithium cobaltate (LiCoO2), lithium nickelate (LiNiO2), lithium manganate (LiMn2O4), lithium nickel-cobalt-manganate (NCM: LiCO 1 / 3 Ni 1 / 3 Mn 1 / 3 O2), lithium nickel-cobalt-aluminate (LiNi 0.8 (CoAl) 0.2 O2), Li 1+x Mn 2-x-y M y O4 (M is one or more metal elements selected from Al, Mg, Co, Fe, Ni, and Zn), such as heterogeneous element-substituted Li-Mn spinel having a composition represented by the foregoing, but is not limited thereto.

[0028] The material of the negative electrode active material is not particularly limited. The negative electrode active material may be, for example, metallic lithium, and may be a material capable of absorbing and desorbing metal ions such as lithium ions. Examples of the material capable of absorbing and desorbing metal ions such as lithium ions include alloy-based negative electrode active materials, carbon materials, lithium titanate (Li4Ti5O 12 ), silicon carbide (SiC), that is, silicon particles and the like, but are not limited thereto.

[0029] The alloy-based anode active material is not particularly limited and includes, for example, Si alloy-based anode active materials or Sn alloy-based anode active materials. Si alloy-based anode active materials include silicon, silicon oxides, silicon carbides, silicon nitrides, etc., or solid solutions thereof. Si alloy-based anode active materials may also contain metallic elements other than silicon, such as iron (Fe), cobalt (Co), antimony (Sb), bismuth (Bi), lead (Pb), nickel (Ni), copper (Cu), zinc (Zn), germanium (Ge), indium (In), tin (Sn), titanium (Ti), etc. Sn alloy-based anode active materials include tin, tin oxides, tin nitrides, etc., or solid solutions thereof. Furthermore, the Sn alloy negative electrode active material may also contain other metallic elements besides tin, such as iron (Fe), cobalt (Co), antimony (Sb), bismuth (Bi), lead (Pb), nickel (Ni), copper (Cu), zinc (Zn), germanium (Ge), indium (In), tin (Sn), titanium (Ti), etc.

[0030] The carbon material is not particularly limited and includes, for example, hard carbon, soft carbon, graphite, and graphite.

[0031] The shape of the active material is not particularly limited and may be particulate, for example. If the active material is particulate, the particle size D of the active material 50 For example, the particle size D may be 1 nm or more, 5 nm or more, or 10 nm or more, and may also be 500 μm or less, 100 μm or less, 50 μm or less, or 30 μm or less. 50 This is the particle diameter (median diameter) at 50% of the integrated value in the volume-based particle size distribution determined by laser diffraction and scattering.

[0032] The content of the active material in the first or second active material layer of this disclosure is not particularly limited, but may be 1% by mass or more, 5% by mass or more, 10% by mass or more, 15% by mass or more, or 20% by mass or more, and may be 50% by mass or less, 45% by mass or less, 40% by mass or less, 35% by mass or less, or 30% by mass or less.

[0033] In this disclosure, the thickness of the first or second active material layer is not particularly limited, but may be, for example, 0.1 μm or more, 1.0 μm or more, 3.0 μm or more, 5.0 μm or more, or 10.0 μm or more, and may be 1000.0 μm or less, 700.0 μm or less, 500.0 μm or less, 300.0 μm or less, or 100.0 μm or less.

[0034] In this disclosure, the density of the first or second active material layer is not particularly limited, but is 0.5 g / cm³. 3 More than 0.7g / cm 3 More than 1.0g / cm 3 More than 1.5g / cm 3 Above, or 2.0 g / cm³ 3 The above is acceptable, and 15.0 g / cm³ 3 Below, 10.0g / cm 3 Below, 8.0g / cm 3 Below, 6.0g / cm 3 Below, 4.0g / cm 3 The following, or 3.0 g / cm³ 3 The following is acceptable:

[0035] In this disclosure, the conductive additive may be contained in the first or second active material layer.

[0036] In this disclosure, the conductive additive optionally included in the first or second active material layer may be one known as a conductive additive for secondary batteries. Specifically, examples of conductive additives include carbon materials such as Ketjenblack (KB), vapor-processed carbon fiber (VGCF), acetylene black (AB), carbon nanotubes (CNT), carbon nanofibers (CNF), carbon black, coke, and graphite. The conductive additive may also be a metallic material that can withstand the environment in which the battery is used. The conductive additive may be used alone or in combination of two or more types. The conductive additive may be in various forms such as powder or fiber.

[0037] In this disclosure, the content of the conductive additive in the first or second active material layer is not particularly limited, but may be 0.1% by mass or more, 0.5% by mass or more, 1.0% by mass or more, 3.0% by mass or more, or 5.0% by mass or more, and may be 20.0% by mass or less, 15.0% by mass or less, 10.0% by mass or less, 8.0% by mass or less, or 5.0% by mass or less.

[0038] In this disclosure, the solid electrolyte optionally included in the first or second active material layer may be one known as a solid electrolyte for secondary batteries. Examples of solid electrolytes include inorganic solid electrolytes such as sulfide solid electrolytes, oxide solid electrolytes, and halide solid electrolytes, and organic polymer electrolytes such as polymer electrolytes. From the viewpoint of heat resistance, sulfide solid electrolytes and oxide solid electrolytes are particularly preferred. The solid electrolyte may be in particulate form, for example. Only one type of solid electrolyte may be used alone, or two or more types may be used in combination.

[0039] Examples of sulfide solid electrolytes include solid electrolytes containing Li, X (where X is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In), and S. The sulfide solid electrolyte may further contain at least one of O and halogen elements. Examples of halogen elements include F, Cl, Br, and I. The sulfide solid electrolyte may be made of glass (amorphous) or glass ceramics. Examples of sulfide solid electrolytes include, but are not limited to, Li2S-P2S5, LiI-Li2S-P2S5, LiI-LiBr-Li2S-P2S5, Li2S-SiS2, Li2S-GeS2, and Li2S-P2S5-GeS2.

[0040] Examples of oxide solid electrolytes include Li7La3Zr2O. 12 Li 7-x La3Zr 1-x Nb x O 12 Li 7-3x La3Zr2Al x O12 Li 3x La 2 / 3-x TiO3, Li 1+x Al x Ti 2-x (PO4)3, Li 1+x Al x Ge 2-x (PO4)3, Li3PO4, or Li 3+x PO 4-x N x Examples include (LiPON), but are not limited to these. The oxide solid electrolyte may be amorphous or crystalline.

[0041] Examples of halogen solid electrolytes include NaBH4 and NaB 10 H 10 NaCB9H 10 NaCB 11 H 12 NaB 12 Cl 12 These are some examples, but are not limited to them.

[0042] Examples of polymer electrolytes include, but are not limited to, polyethylene oxide (PEO), polypropylene oxide (PPO), and copolymers thereof.

[0043] The content of the solid electrolyte optionally included in the first or second active material layer of this disclosure is not particularly limited, but may be 1.0% by mass or more, 5.0% by mass or more, 10.0% by mass or more, 13.0% by mass or more, or 15.0% by mass or more, and may be 30.0% by mass or less, 20.0% by mass or less, 15.0% by mass or less, or 10.0% by mass or less.

[0044] In this disclosure, the binder optionally included in the first or second active material layer may be one known as a binder used in secondary batteries. Examples of binders include styrene-butadiene rubber (SBR), carboxymethylcellulose (CMC), acrylonitrile-butadiene rubber (ABR), butadiene rubber (BR), polyvinylidene fluoride (PVDF), and polytetrafluoroethylene (PTFE). The binder may be used alone or in combination of two or more types.

[0045] The binder content optionally included in the first or second active material layer of this disclosure is not particularly limited, but may be 0.1% by mass or more, 0.5% by mass or more, 1.0% by mass or more, 3.0% by mass or more, or 5.0% by mass or more, and may be 20.0% by mass or less, 15.0% by mass or less, 10.0% by mass or less, 8.0% by mass or less, or 5.0% by mass or less.

[0046] (Current collector foil) In this disclosure, the current collector foil is included in the electrode laminate precursor and the electrode laminate.

[0047] Examples of materials for current collector foil include, but are not limited to, aluminum, aluminum alloys, and stainless steel.

[0048] The thickness of the current collector foil is not particularly limited, but may be 20 μm or more, 30 μm or more, or 40 μm or more, or it may be 70 μm or less, 60 μm or less, or 50 μm or less.

[0049] <Process (a)> The present disclosure provides a method for manufacturing a bipolar electrode laminate, which first provides an electrode laminate precursor having a first active material layer precursor, a current collector foil, and a second active material layer precursor in that order.

[0050] (Electrode stack precursor) In this disclosure, the electrode laminate precursor comprises a first active material layer precursor, a current collector foil, and a second active material layer precursor in that order. In this disclosure, a bipolar electrode laminate can be obtained by pressing the electrode laminate precursor.

[0051] Details of the current collector foil included in the electrode laminate precursor in this disclosure can be found in the above description relating to the bipolar electrode laminate in this disclosure.

[0052] (First and second active material layer precursors) In this disclosure, the first and second active material layer precursors are included in the electrode stack precursor.

[0053] In this disclosure, the first active material layer precursor contains ethylene carbonate. In this configuration, the second active material layer precursor may or may not contain ethylene carbonate.

[0054] In this disclosure, the ethylene carbonate content in the first active material layer precursor is greater than the ethylene carbonate content in the second active material layer precursor. The ethylene carbonate content in the first and second active material layer precursors is not particularly limited, but may be 0.5 wt% or more, 0.8 wt% or more, 1.0 wt% or more, or 1.5 wt% or more, and may also be 10.0 wt% or less, 9.0 wt% or less, 8.0 wt% or less, or 6.0 wt% or less.

[0055] Details of the active material, dispersant, conductive additive, solid electrolyte, and binder contained in the first and second active material layer precursors of this disclosure can be found in the above description relating to the bipolar electrode stack of this disclosure.

[0056] <Process (b)> In the method of manufacturing a bipolar electrode stack according to the present disclosure, the electrode stack precursor is then pressed with a pressing member. In the method of the present disclosure, in step (b), the ethylene carbonate is at least partially melted.

[0057] (Pressed parts) In this disclosure, a pressing member is used to press the electrode laminate precursor.

[0058] In this disclosure, the temperature of the press member is not particularly limited, but may be 40°C or higher, 50°C or higher, 60°C or higher, or 80°C or higher, and may be 150°C or lower, 140°C or lower, 130°C or lower, or 120°C or lower. In this disclosure, the temperature of the press member may be above the melting point of ethylene carbonate. This makes it easier to melt the ethylene carbonate contained in the first and / or second active material layer precursor when pressing the electrode laminate precursor with the press member.

[0059] In this disclosure, the pressing pressure is not particularly limited, but may be 0.2 kN / cm or more, 0.4 kN / cm or more, 0.6 kN / cm or more, or 0.8 kN / cm or more, and may be 5.0 kN / cm or less, 4.5 kN / cm or less, 4.0 kN / cm or less, or 3.5 kN / cm or less.

[0060] In this disclosure, the type of press member is not particularly limited, but the press member may be a roll press, and is preferably a roll press. When the press member is a roll press, the diameter of the press roll is not particularly limited.

[0061] The present disclosure will be further described with reference to the following embodiments, but the scope of the present disclosure is not limited to these embodiments. [Examples]

[0062] ≪Example 1≫ <Preparation of active material slurry> A slurry of the positive electrode active material, conductive additive, dispersant, binder, and ethylene carbonate was prepared by kneading them in predetermined proportions. At this time, the ethylene carbonate content in the active material layer slurry was 2.7 wt%.

[0063] <Preparation of the active material layer precursor> The prepared active material slurry was coated onto a current collector foil to create an active material layer precursor. The active material layer precursor was dried at 100°C for 10 minutes.

[0064] <Pressing of the active material layer precursor> The dried active material precursor was roll-pressed under the following conditions to produce the active material layer: Press roll diameter: Φ125cm, Roll temperature: 80℃, Press load: 0.6 kN / cm.

[0065] <Evaluation of the active material layer> The ethylene carbonate content in the active material layer after pressing was measured using GC-MS analysis. Furthermore, the active material layer was punched out with a diameter of φ11.28 mm, and the weight (mg) and thickness (μm) of the punched-out active material layer were measured. The density of the active material layer was then calculated using the following formula: (Density of the active material layer) = (Weight of the active material layer) / (Thickness of the active material layer) × 10

[0066] Furthermore, the density of the active material layer excluding ethylene carbonate was calculated using the following formula: (Density of the active material layer) = {(Weight of the active material layer) - (Ethylene carbonate content)} / (Thickness of the active material layer) × 10

[0067] Example 2 An active material layer according to Example 2 was prepared in the same manner as in Example 1, except that the ethylene carbonate content in the active material layer precursor was set to 5.3 wt%.

[0068] ≪Comparative Example 1≫ The active material layer according to Comparative Example 1 was prepared in the same manner as in Example 1, except that the active material layer precursor did not contain ethylene carbonate.

[0069] The conditions for implementation and evaluation results for Comparative Example 1 and Examples 1 and 2 are shown in Table 1 below.

[0070] [Table 1]

[0071] As is clear from Table 1 above, Examples 1 and 2, in which the active material layer precursor contained ethylene carbonate, showed a higher "density of the active material layer excluding ethylene carbonate" compared to Comparative Example 1, in which the active material layer precursor did not contain ethylene carbonate. Furthermore, Example 2, which contained a larger amount of ethylene carbonate in the active material layer precursor, showed an even higher "density of the active material layer excluding ethylene carbonate" compared to Example 1. From the above, it was confirmed that a high-density active material layer can be produced by pressing an active material layer precursor containing ethylene carbonate and partially melting the ethylene carbonate contained in the active material layer precursor during pressing.

Claims

1. A method for manufacturing a bipolar electrode laminate having a first active material layer, a current collector foil, and a second active material layer in this order, (a) To provide an electrode laminate precursor having a first active material layer precursor, a current collector foil, and a second active material layer precursor in this order, and (b) Pressing the electrode laminate precursor with a pressing member, Includes, The first active material layer precursor contains ethylene carbonate, The ethylene carbonate content in the first active material layer precursor is greater than the ethylene carbonate content in the second active material layer precursor, and In step (b), the ethylene carbonate is melted at least partially. A method for manufacturing a bipolar electrode stack.

2. The method according to claim 1, wherein the temperature of the press member is at or above the melting point of ethylene carbonate.

3. The method according to claim 1, wherein the pressing member is a roll press.

4. The method according to claim 1, wherein the first active material layer is a positive electrode active material layer, and the second active material layer is a negative electrode active material layer.

5. The method according to claim 4, wherein the negative electrode active material layer contains silicon particles as a negative electrode active material.

Citation Information

Patent Citations

  • Active material layer coating composition, electrode plate, manufacturing method of them, and nonaqueous electrolyte secondary battery

    JP2006107749A

  • Coating composition for active material layer, electrode board, its manufacturing method and nonaqueous electrolyte secondary battery

    JP2006172805A

  • Electrode manufacturing method

    JP2021082504A

  • Manufacturing method of bipolar electrode laminate, and manufacturing method of bipolar battery

    JP2024175966A